Application of fuzzy systems to support the development of a socioenvironmental sustainability index applied to river basins - Collins da Cunha e Silva, Darllan [UNESP]; Angrizani de Oliveira, Renan [UNESP]; Cezar Simonetti, Vanessa [UNESP]; de Lima Andrade, Erik [UNESP]; Ana Paixão de Sousa, Jocy [UNESP]; Costa Abreu Sales, Jomil [UNESP]; Wagner Lourenço, Roberto [UNESP] (Taylor & Francis, 2021)
Socioenvironmental indexes are important mechanisms for the communication of information in a summary form. They may also be a sound source on the quality of life of human beings. In this sense, the objective of this research is to create a socioenvironmental sustainability index (SSI) applied to river basins that integrate socioenvironmental information from the river basin of the Una River in São Paulo (Brazil) by creating a fuzzy inference system in a geographic information system environment. From the results obtained, only two sub-river basins of the Una River are classified as regular. They are in the urban area to the north of the study area. The other sub-river basins are classified as in poor conditions, that is, with high socioenvironmental vulnerability. They correspond to 81% of the study area. This poor classification is justified by the low income and the high rate of illiteracy in the study area. Both factors presented very poor values. The urban area, compared to the rural area, showed a better socioenvironmental performance. It is partly justified by the access of the population in these areas to education and better work opportunities.
Keywords: AHP; geoprocessing; index; River basin; socioenvironmental vulnerability